Growth and Labor Income Risk with Inelastic and Elastic Labor Supply - Christiane Clemens (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
We discuss long-run growth in an economy which is subject to aggregate productivity shocks affecting all factors of production. We demonstrate that the presence of labor income risk unambiguously is an important determinant of long-run expected growth. The issue of dynamic inefficiency of the underlying allocation is related to the size of the risk premium on capital return. The paper also examines the effects distributive disturbances and elastic labor supply, the latter giving rise to the possibility of multiple equilibria.
Keywords: D9; D8; O4; 330; income risk; labor supply; endogenous growth